Gender Issues in Keluarga Berencana Programs: An Analysis of the Concept of Mubadalah and the Islamic Perspective on Male Contraception - Avrizal Akhmad Setiawan; Aza Ria Audina (SUHU: Journal of Sufism and Humanities, 2026)
Objective: This study examines the application of the mubādalah approach in promoting the equitable distribution of reproductive responsibilities between husband and wife and analyzes the Islamic perspective on male contraception within family planning (Keluarga Berencana). Method: This study employs a library research approach by critically reviewing books, scholarly journal articles, and classical and contemporary Islamic legal literature on family planning, mubādalah, gender relations, and Islamic jurisprudence. Data were analyzed using qualitative content analysis, while source triangulation enhanced the credibility of the findings. Results: Previous studies on family planning from an Islamic perspective have primarily focused on the permissibility or prohibition of contraceptive methods, with limited attention to gender inequality in reproductive responsibilities. In Indonesia, contraceptive use remains dominated by women, whereas male participation is relatively low. The mubādalah approach offers an alternative framework emphasizing reciprocity, partnership, and shared responsibility between spouses in reproductive decision-making. According to Islamic law, temporary male contraceptive methods, including ‘azl (coitus interruptus) and condoms, are generally permissible when intended for birth spacing and when they do not cause harm. Conversely, permanent methods such as vasectomy are generally prohibited unless justified by legitimate medical necessity. Conclusion: Integrating the mubādalah approach into family planning discourse promotes gender-equitable reproductive responsibility, strengthens shared decision-making between spouses, and provides a normative foundation for increasing male participation in family planning programs in Indonesia.